Surgical treatment of lumbar spinal stenosis with microdecompression and interspinous distraction device insertion. A case series - Ploumis, Avraam (BioMed Central, 2012)
BACKGROUND: Interspinous distraction devices (IPDD) are indicated as stand-alone devices for the treatment of spinal stenosis. The purpose of this study is to evaluate the results of patients undergoing surgery for spinal stenosis with a combination of unilateral microdecompression and interspinous distraction device insertion. METHODS: This is a prospective clinical and radiological study of minimum 2 years follow-up. Twenty-two patients (average age 64.5 years) with low-back pain and unilateral sciatica underwent decompressive surgery for lumbar spinal stenosis. Visual Analogue Scale, Oswestry Disability Index and walking capacity plus radiologic measurements of posterior disc height of the involved level and lumbar lordosis Cobb angle were documented both preoperatively and postoperatively. One-sided posterior subarticular and foraminal decompression was conducted followed by dynamic stabilization of the diseased level with an IPDD (X-STOP). RESULTS: The average follow-up time was 27.4 months. Visual Analogue Scale and Oswestry Disability Index improved statistically significantly (p < 0.001) in the last follow-up exam. Also, the walking distance increased in all patients but two. Posterior intervertebral disc height of the diseased level widened average 1.8 mm in the postoperative radiograph compared to the preoperative. No major complication, including implant failure or spinous process breakage, has been observed. CONCLUSIONS: The described surgical technique using unilateral microdecompression and IPDD insertion is a clinically effective and radiologically viable treatment method for symptoms of spinal stenosis resistant to non-operative treatment.